Los sistemas de comercialización y el nivel de ingresos de la farmacia el alquimista en Riobamba, período 2017-2018 - Andino Rodríguez, Nataly Silvana (2019)
This research "THE SYSTEMS OF COMMERCIALIZATION AND THE LEVEL OF INCOMES OF ALCHEMIST PHARMACY IN RIOBAMBA, PERIOD 2017-2018", was developed with the purpose of contributing to solve problems that have generated the misuse of the systems of commercialization, affecting the income. the objectives proposed to determine each of the problems the pharmacy faced in the application of its sales system. The framework includes the background, the theoretical foundation and the research units that are described as follows: Unit I: The Alchemist Pharmacy, Unit II: Commercialization systems, Unit III: Incomes. The methodological framework describes the method, types and designs of research, population and sample, techniques and instruments for gathering information, as well as information procedure, analysis and interpretation of results. Furthermore, the study presents the conclusions and recommendations established in the investigation, and the proposal. Finally, the bibliography and the corresponding annexes to the research are also attached.